2017
DOI: 10.4103/ccd.ccd_147_17
|View full text |Cite|
|
Sign up to set email alerts
|

Comparative alveolar ridge preservation using allogenous tooth graft versus free-dried bone allograft: A randomized, controlled, prospective, clinical pilot study

Abstract: Background:For the first time in India, allografts from human extracted teeth were prepared. A randomized, prospective, clinicoradiographical, histological study was conducted to evaluate their efficacy in comparison with freeze-dried bone allograft (FDBA) in alveolar ridge preservation.Materials and Methods:Graft preparation: with written consent, teeth were collected from three donors (full mouth extraction cases). Once donors’ serums were tested negative for HIV, HBV, HCV, and Venereal disease research labo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 20 publications
1
29
0
6
Order By: Relevance
“…The estimated effect size given for comparison of the groups was 2.049, based on a previous study [15]. It was determined that a sample set of nine participants per group would be required to recognize a significant difference regarding the ridge width of the CBCT, with 80% power and a 5% confidence level.…”
Section: Statistical Analysesmentioning
confidence: 99%
See 3 more Smart Citations
“…The estimated effect size given for comparison of the groups was 2.049, based on a previous study [15]. It was determined that a sample set of nine participants per group would be required to recognize a significant difference regarding the ridge width of the CBCT, with 80% power and a 5% confidence level.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…Several recent studies have demonstrated that DDM is well-tolerated when used to fill the ridge defects, indicating promising potential for bone regeneration [13][14][15]20]. Similarly, the effectiveness of DDM as a bone substitute has already been identified in various clinical circumstances such as the alveolar bone regeneration associated with dental implants, sinus augmentation, and preservation of extraction sockets [13][14][15]21,22]. In these studies, DDM completely fulfills the criteria for a bone regeneration material, possessing osteoinductive and osteoconductive properties [23].…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…[6] Briefly, full-mouth extraction cases were screened to identify potential donors to collect extracted teeth. Four patients with nonreactive sera for HIV, hepatitis B virus, hepatitis C virus, and syphilis antigens donated their extracted teeth.…”
Section: Case Reportmentioning
confidence: 99%